Molecular analysis of the phoH gene, belonging to the phosphate regulon in Escherichia coli. - Kim, S K (1993)
By making operon fusions with lambda placMu53, we identified, cloned, and analyzed the phoH gene belonging to the phosphate (pho) regulon. We mapped the phoH gene at 23.6 min in the Escherichia coli genomic library (Y. Kohara, K. Akiyama, and K. Isono, Cell 50:495-508, 1987). Its nucleotide sequence revealed an open reading frame of 354 amino acids which contains sequences for nucleotide-binding motifs. From comparison of the DNA sequences, phoH was found to be identical to psiH, which had been identified as a phosphate starvation-inducible gene (W.W. Metcalf, P.M. Steed, and B.L. Wanner, J. Bacteriol. 172:3191-3200, 1990). The PhoH protein was overproduced by the T7 promoter system, identified as a protein of about 39 kDa, and purified. The amino-terminal amino acid sequence of the PhoH protein agreed with the one deduced from the DNA sequence. We demonstrated that PhoH has an ATP-binding activity by a photoaffinity labeling experiment. Two transcriptional initiation sites (P1 and P2) were identified by S1 nuclease mapping. The upstream P1 promoter contains a pho box, the conserved sequence shared by the pho regulon genes. The region containing the pho box was bound by PhoB protein, the transcriptional activator of the pho regulon, as revealed by footprinting. Regulation of phoH expression in vivo was studied by constructing plasmids containing transcriptional fusions of the phoH promoters with a promoterless gene for chloramphenicol acetyltransferase. Transcription from the P1 promoter required the phoB function and was induced by phosphate limitation, while transcription from the P2 promoter was independent of phoB and constitutive under tested conditions.